2019
DOI: 10.5114/aoms.2017.68535
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin ameliorates mucosal tissue injury of mesenteric ischemia and reperfusion in an experimental rat model

Abstract: Introduction: Mesenteric ischemia/reperfusion (I/R) injury is a serious clinical condition. There were a lot of experimental studies performed in the treatment of I/R injury. To our knowledge, this is the first experimental study with effects of sesamin on I/R injury model. We aimed to investigate the protective effect of sesamin on mesenteric I/R injury model. Material and methods: A total of 32 male Sprague-Dawley rats were divided into four groups. Control group: superior mesenteric artery (SMA) exposed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…36 It was found that I/R injury was accompanied with excess oxygen-free radicals, which caused cell membrane lipid peroxidation, membrane damage, inhibition of mitochondrial activity, and augmented membrane permeability. 37 Furthermore, Chen et al 38 mentioned that the generation of an extreme amount of reactive oxygen species (ROS) in injured cells and tissues during I/R lesion triggered different signaling pathways, promoted inflammatory reactions, and damaged the function of the intestinal mucosal barrier. Our results regarding the state of oxidant/antioxidant imbalance in I/R control group were in line with the results of Mohamed and Almallah 39 and Tassopoulos et al 40 who demonstrated that the MDA level is considered a consistent indicator of an I/R incident, and it increases with the severity of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…36 It was found that I/R injury was accompanied with excess oxygen-free radicals, which caused cell membrane lipid peroxidation, membrane damage, inhibition of mitochondrial activity, and augmented membrane permeability. 37 Furthermore, Chen et al 38 mentioned that the generation of an extreme amount of reactive oxygen species (ROS) in injured cells and tissues during I/R lesion triggered different signaling pathways, promoted inflammatory reactions, and damaged the function of the intestinal mucosal barrier. Our results regarding the state of oxidant/antioxidant imbalance in I/R control group were in line with the results of Mohamed and Almallah 39 and Tassopoulos et al 40 who demonstrated that the MDA level is considered a consistent indicator of an I/R incident, and it increases with the severity of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…interferon γ (IFNγ)-inducible protein 10 (IP-10/CXCL10)) in human primary monocytes and THP-1 cells ( Hsieh et al, 2014 ). The anti-inflammatory effects of sesamin have also been observed in different in vivo models ( Cui et al, 2010 , Lin et al, 2014 , Ahmad et al, 2016 , Zhang et al, 2016 , Li et al, 2016 , Fan et al, 2017 , Rousta et al, 2018 , Zhao et al, 2019 , Bai et al, 2019 , Lin et al, 2019 , Sayhan et al, 2019 Ali et al, 2020 ). Consistently, sesamin has been shown to suppress a series of inflammatory markers associated with type-II diabetes and rheumatoid arthritis in humans ( Mohammad Shahi et al, 2017 , Helli et al, 2019 ).…”
Section: Anti-inflammatory Effects Of Sesaminmentioning
confidence: 90%
“…* * P < 0:01 and * * * P < 0:001 vs. the sham group; # P < 0:05, ## P < 0:01, and ### P < 0:001 vs. the I/R and H/R group. 6 Oxidative Medicine and Cellular Longevity reversed by sesamin (Figure 4(e)), suggesting that sesaminreduced intestinal I/R injury was related to the inhibition of oxidative stress. Nrf2 activation is related to suppression of oxidative stress.…”
Section: Resultsmentioning
confidence: 92%
“…Sesamin (Figure 1), a natural lignin compound, is isolated from sesame seeds, and it possesses health beneficial effects, including anti-inflammatory, anticancer, antihypertensive, antithrombotic, antidiabetic, antiatherogenic, antiobesity, and lipolytic effects [4,5], and ameliorates intestinal, renal, cardiac, brain, and hepatic injury [6][7][8][9][10][11]. However, the key modulatory properties and characteristics of sesamin and related mechanisms in ameliorating intestinal I/R injury remain to be explored.…”
Section: Introductionmentioning
confidence: 99%